Bulk Metallic Glasses for Implantable Medical Devices and Surgical Tools. Issue 27 (31st March 2016) - Meagher, Philip; O'Cearbhaill, Eoin D.; Byrne, James H.; Browne, David J.
Abstract : With increasing knowledge of the materials science of bulk metallic glasses (BMGs) and improvements in their properties and processing, they have started to become candidate materials for biomedical devices. A dichotomy in the types of medical applications has also emerged, in which some families of BMGs are being developed for permanent devices whilst another family – of Mg‐based alloys – is showing promise in bioabsorbable implants. The current status of these metallurgical and technological developments is summarized. Abstract : Bulk metallic glasses are becoming candidate materials for biomedical devices, with continuous improvements in their processing and properties. A dichotomy in application types is apparent, in which some families of BMGs are being developed for permanent devices whilst another family – that of Mg‐based alloys – shows promise in bioabsorbable implants. The current status of these metallurgical and technological developments is summarized.